2011
DOI: 10.1063/1.3662963
|View full text |Cite
|
Sign up to set email alerts
|

35.4 T field generated using a layer-wound superconducting coil made of (RE)Ba2Cu3O7−x (RE = rare earth) coated conductor

Abstract: To explore the limits of layer wound (RE)Ba 2 Cu 3 O 7-x (REBCO, RE = Rare Earth) coils in a high magnetic field environment > 30 T, a series of small insert coils have been built and characterized in background fields. One of the coils repeatedly reached 35.4 T using a single ~100 m length of REBCO tape wet wound with epoxy and nested in a 31 T background magnet. The coil was quenched safely several times without degradation. Contributing to the success of this coil was the introduction of a thin polyester fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
99
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(102 citation statements)
references
References 9 publications
(12 reference statements)
1
99
0
1
Order By: Relevance
“…%Ti wires, in which α-Ti precipitates yield significant pinning enhancement. 21 F p (H//c) for the 15% Zr-doped film at 77 K is comparable to that of optimized Nb-Ti at 4.2 K, which is ∼16.9 GN/m 3 at ∼5 T. Strikingly, H irr (77 K) ∼14.8 T for the 15% thin film is even higher than the H irr ∼ 11 T of Nb-Ti at 4.2 K. An earlier work using BaSnO 3 and BZO has achieved F p (H//c) > 25 GN/m 3 but peaking at somewhat lower field and without any H irr (T) measurement. 16 J c (H//c) at 4.2 K and H up to 31.2 T of both 7.5 and 15 mol.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…%Ti wires, in which α-Ti precipitates yield significant pinning enhancement. 21 F p (H//c) for the 15% Zr-doped film at 77 K is comparable to that of optimized Nb-Ti at 4.2 K, which is ∼16.9 GN/m 3 at ∼5 T. Strikingly, H irr (77 K) ∼14.8 T for the 15% thin film is even higher than the H irr ∼ 11 T of Nb-Ti at 4.2 K. An earlier work using BaSnO 3 and BZO has achieved F p (H//c) > 25 GN/m 3 but peaking at somewhat lower field and without any H irr (T) measurement. 16 J c (H//c) at 4.2 K and H up to 31.2 T of both 7.5 and 15 mol.…”
mentioning
confidence: 68%
“…We ascribe the excellent pinning performance at high temperatures to the high density (equivalent vortex matching field ∼7 T) of self-assembled BZO nanorods, while the low temperature pinning force is enhanced by large additional pinning which we ascribe to strain-induced point defects induced in the REBCO matrix by the BZO nanorods. Our results suggest even more room for further performance enhancement of commercial REBCO coated conductors and point the way to REBCO coil applications at liquid nitrogen temperatures since the critical current density J c (H//c) characteristic at 77 K are now almost identical to those of fully optimized Nb-Ti at 4 Thanks to its high critical temperature T c , high critical current density J c , high irreversibility field H irr , and moderate anisotropy parameter γ , REBa 2 Cu 3 O x (REBCO, where RE = rare earth) thin films grown on flexible and mechanically strong substrates can exceed the temperature and field application limits of the Nb-based low temperature superconductors, and enable superconducting applications in a broad temperature and magnetic field regime now exceeding 35 T at 4 K. [1][2][3] However, further J c and H irr enhancement and anisotropy reduction are strongly desirable for compelling, costeffective applications, and especially to enable multi-Tesla fields in a temperature regime of 30-77 K. [4][5][6] Enhanced vortex pinning is needed both to raise higher temperature irreversibility fields and to raise J c so that overall conductor current density J E can reach the required high values of the order of 500 A/mm 2 . Adding higher densities of nanoscale defects with strong vortex pinning properties is the most efficient strategy.…”
mentioning
confidence: 99%
“…On the other hand, REBa 2 Cu 3 O x (RE-123; RE:rare earth) coated conductor tape is used and insert magnet for high magnetic field generation is fabricated [9]. Degradation of the performance of RE-123 double-pancake coil due to epoxy impregnation is investigated and it is found that dry winding and paraffin impregnation suppress degradation [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported by some workers that testing of second generation tape sometimes resulted in delamination of the tapes when using resin based insulation systems for wound coils [4][5][6][7]. One proposed root cause is the differential thermal contraction between the coil former (the mechanical structure upon which the coil is wound) and the resin encapsulated coil turns resulting in the tape caxis (direction normal to tape length and widest tape face) tensile stress being exceeded.…”
Section: Introductionmentioning
confidence: 99%